From Condemnation to Cooperation: The Evolution of China’s Position toward UN Peacekeeping Operations - Chávez Mazuelos, Jorge Antonio (2023)
In its capacity as a great power, China has assumed greater responsibilities regarding the provision of global public goods. Therefore, it has become the UN Security Council’s permanent member which contributes the largest amount of troops to peacekeeping operations. Consequently, China has steadily increased its financial contributions and registered an 8.000 peacekeeping stand-by force. Nonetheless, China’s current leadership in the field of peacekeeping operations differs radically from its initial rejection for missions which it regarded as imperialist instruments destined to undermine the progress of revolutionary movements and weaken the principle of sovereignty. Therefore, in this article, I will explain the evolution of China’s stance toward UN PKOs from an outright rejection to a moderate opposition, and from a limited support to an active participation. Furthermore, I will explain how PKOs enable China to protect its national interests in conflict zones and upgrade its military capabilities through military operations other than war. (MOOTW). Finally, I will explain that this stance is the reflection of evolving national conception roles and of a more ambitious Chinese foreign policy; through which Beijing seeks to strengthen international cooperation, safeguard its interests and nationals overseas, redefine international norms and global governance schemes and reaffirm its great power status.